ANALISIS KEBUTUHAN RUANG TERBUKA HIJAU BERDASARKAN PERTUMBUHAN PENDUDUK DAN PERTAMBAHAN KENDARAAN BERMOTOR UNTUK PENGEMBANGAN WILAYAH DI KOTA KENDARI - Muhamamad Idham Handa (Universitas Halu Oleo, 2016)
Muhammad Idham Handa G2F1 011 017 Needs Green Space Based on population growth andAdded Number of motor vehicles for Regional Development in Kendari, under the guidancecounselor Mrs. Weka Widayati as I and Mr. La Baco Sudia, as supervisor II.The need for green open space in urban areas is very meaningful to the people who are on it,causing a variety of multifunctional green space in urban tend to be kept and preserved andallocated. Aesthetic function, the function of water absorption, keeping the microclimate and donot forget to also function providers of oxygen (O2) for a living. In fact population growth is one ofthe factors that cause a reduction in green space, on the other hand increase the number of motorvehicles also require the presence of green space as an absorber of pollutants (CO2) so it needs away out to overcome this problem.The purpose of this study was to analyzed existing condition green space in the city of Kendari, thesecond is to analyze the need for green space based on population growth and the rate of motorvehicle in the city of Kendari, and the last is to analyze the balance of the needs and theavailability of green space and green space allocation plan in Kendari on future to come. Theanalysis used in its entirety is a qualitative descriptive analysis where the growth of populationand the number of vehicles projected and green space per resident in need of analysis inaccordance with existing regulations and previous research.The results showed that the condition of the existing green space in the city of Kendari in 2011covering an area of 3777.46 Ha is, each spread over ten (10) districts with diverse typologies.Kendari City residents need green space in 2011 amounted to 511.625 ha while the need for greenspace by the growing number of motor vehicles is 0.28 ha. Balance of green space needs based onthe remaining population of 2470.49 ha, in the 30 years to come RTH allocated to areas with ahigh density and on roads with high density.Keywords: Green Open Space, Population, Added Motor Vehicles, Existing green space and greenspace needs